Physical Quality of Some Biomass Briquettes - Wakchaure, G C; Sharma, P K (Journal of Agricultural Engineering, 2007)
This paper deals with the effect of material and concentration of binders on the physical quality of biomass briquettes. The briquettes were prepared using tree leaves, saw dust and wheat straw. Two binding materials namely, molasses and sodium silicate at varying concentration were used in the preparation of briquettes. The Saw dust and wheat straw briquettes could not be formed when concentration of binder was below 10% whereas formation of tree leaves briquettes was possible even without use of any binding materials. Sodium silicate was found a better binding agent than molasses for briquette preparation. The bulk density of briquettes of tree leaves, saw dust and wheat straw with molasses as binder was observed as 3.5, 6.3 and 3.8 times of the bulk density of respective raw materials. The study revealed that among all types of briquettes, saw dust briquettes with sodium silicate at 25% concentration were better in terms of compressive strength, shattering resistance, bulk density and calorific value and hence better for transportation, storage and for burning purposes.